Urinary volume and sodium excretion potassium and creatinine in 24 hours - Gamarra Alvarez, Miguel (1958)
We have studied a group of 97 young subjects, almost all medical students. 24-hour urine collections were made on them and the urinary volume and sodium, potassium and creatinine were studied. The study was conducted during two consecutive years and preliminary data allowed to make the division into groups (22 ° C Temp.media.) (14 ° C Temp.media.) Summer and winter, in terms in urine volume and sodium and potassium.